The Effect of Temperature on Bipolar Junction Transistor Noise - Shah, Narendra K. (My University, 1972)
The effect on temperature on the noise characteristics at mid-frequencies of a low-noise silicon bipolar junction transistor is investigated theoretically and experimentally. Over a range of temperatures, an optimum device temperature is sought, and base resistance data is obtained from the noise measurements.
Title: The Effect of Temperature on Bipolar Junction Transistor Noise, Author: Narendra K. Shah, Location: Thode